PLANES Y POBREZA EN CÓRDOBA (ARGENTINA). REFLEXIONES ACERCA DE LAS POLÍTICAS SOCIOLABORALES DESDE EL ESTUDIO DE SU IMPLEMENTACIÓN - Gutiérrez, Alicia B. (Universidad de Costa Rica, 2013)
This article refers to the different stages of social policies in Argentina and how they have developed within the historical context. Afterwards, from the first results of the analysis of the implementation of two plans in a poor community of Cordoba, a province of Argentina, we propose some reflections about fundamental decisions of three types: theoretical-political decisions, theoretical-instrumental decisions and theoretical-methodologic decisions.